Discovery of Nanosota-EB1 and -EB2 as Novel Nanobody Inhibitors Against Ebola Virus Infection. - Fan Bu; Gang Ye; Kimberly Morsheimer; Alise Mendoza; Hailey Turner-Hubbard; Morgan Herbst; Benjamin Spiller; Brian E Wadzinski; Brett Eaton; Manu Anantpadma; Ge Yang; Bin Liu; et al. (PLoS Pathogens)
The Ebola filovirus (EBOV) poses a serious threat to global health and national security. Nanobodies, a type of single-domain antibody, have demonstrated promising therapeutic potential. We identified two anti-EBOV nanobodies, Nanosota-EB1 and Nanosota-EB2, which specifically target the EBOV glycoprotein (GP). Cryo-EM and biochemical data revealed that Nanosota-EB1 binds to the glycan cap of GP1, preventing its protease cleavage, while Nanosota-EB2 binds to critical membrane-fusion elements in GP2, stabilizing it in the pre-fusion state. Nanosota-EB2 is a potent neutralizer of EBOV infection in vitro and offers excellent protection in a mouse model of EBOV challenge, while Nanosota-EB1 provides moderate neutralization and protection. Nanosota-EB1 and Nanosota-EB2 are the first nanobodies shown to inhibit authentic EBOV. Combined with our newly developed structure-guided in vitro evolution approach, they lay the foundation for nanobody-based therapies against EBOV and other viruses within the ebolavirus genus.